Management of the Sequelae of a Sport-Related Traumatic Dental Injury Using Ultrasound Examination in the Diagnosis and Follow-Up - Musu, Davide (Dent J (Basel), 2021)
About a quarter of all oral pathologies involving the oral cavity and dental apparatus are traumatic injuries, and a substantial number of these cases are the result of sports injuries affecting adolescents and young adults. Here, we report the case of a 25-year-old healthy female referred to the department of Endodontics for the evaluation and management of teeth 1.2 and 1.1 because of a chronic apical abscess in an area involved in a sport-related dental trauma in the past. A multi-modular diagnostic assessment, comprising conventional periapical radiographs, CBCT imaging, ultrasound, and histopathologic examination, led to a final diagnosis of an apical granulomatous lesion connected to both teeth, and an associated sinus tract. During the follow-up period of three years, the patient was reviewed twice a year and showed progressive healing of the bone and absence of the sinus tract. The present report shows the challenges of diagnosing complications arising from past dental trauma. Furthermore, it is the first documented traumatic case where ultrasound examination was fruitfully used. Emphasis should be put on introducing diagnostic ultrasound for the management of both apical periodontitis and the related sinus tract.